Sustainable Human Resource Management - Ehnert, Ina (PhysicaVerlag HD, 2012)
This book gives new answers to these questions: - How can HRM contribute to attracting, developing and retaining highly qualified human resources over time? - How can a paradox perspective contribute to understanding and coping with paradoxical tensions? - How can sustainability be used as a ‘deliberate strategy’ for HRM?